Penerapan Teknik Editing Animasi Kinetic Typography Pada Pencegahan Penyebaran Virus COVID-19 Di Desa Jipang - Moh Inwan Baikuni; Abednego Dwi Septiadi; Dhanar Intan Surya Saputra (STMIK Sumedang, 2020)
Most of the village of jipang had not fully grasped the knowledge of covid-19 in terms of its spread and prevention. The information that is presented to the community only using verbal means so that the spread of information on the covid-19 is less than optimal and cause concern and anxiety in the face of the covid-19. Therefore media tools as communication tools play a very important role in informing to the community. Researches makes video technique kinetic typography that are meant to the community and anticipation of how the covid-19 are released. The study uses data collection methods conducted using fact finding techniques, work environment observations interviews and planning. The research result consists of covid-19 spread prevention videos the uses technique editing kinetic typography the uses testing alpha beta testing.